KEANEKARAGAMAN JENIS-JENIS LABA-LABA (Arachnida) DI HUTAN PETUANAN DESA RUMAH TIGA KOTA AMBON DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR MATA KULIAH ZOOLOGI INVERTEBRATA - Kuway, Cresensia; Tuaputty, Hasan; Salmanu, Sriyanti Imelda Aksamina; Latupeirissa, Louvenska Nona (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: The diversity of spider species is greatly influenced by the stability of the community of a spider species in a forest ecosystem and the presence of plant vegetation as spider habitat. Forest damage will have an impact on spider diversity which affects the cycle of nutrients and materials in the ecosystem. Biodiversity is a term that includes genes, plant, animal and microorganism species as well as ecosystems and ecological processes Methods: This research is a quantitative descriptive research, namely to calculate the diversity of spider types (Arachnida) in the petuanan forest of Rumah Tiga Village, Ambon Island. Results: There were 6 species of spiders (Arachnida) found in the forests of Taeno, Air Ali and Kranjang hamlets, including P. phalangioides, T. extensa, Araneus diadematus, Menemerus bivittatus, N. pilipes, and C. mildei. Conclusion: The level of diversity (Arachnida) at the research location located in the Taeno hamlet forest is H' 0.68, Air Ali is H' 0.64 and Kranjang is H' 0.60. Judging from the Shannon-Wiener criteria, if the diversity result = <1, diversity is classified as low.